Comments on “Technology and Organizational Government: A Speculative Inquiry into the Functionality of Management Creeds,” by William G. Scott - Davis, Keith (Academy of Management Journal, 1968)
The article presents a response to the paper ?Technology and Organizational Government: A Speculative Inquiry Into the Functionality of Management Creeds,? by William G. Scott, which was published in the September 1968 issue of this journal. The author focuses on two of Scott's conclusions. First, the author takes issue with Scott's claims that human relations seeks to take power away from management and give it to the people. The author claims that human relations really hopes to increase power with both managers and workers. Additionally, the author clams that Scott has underplayed the role of constitutionalism in his discussion of humanism, constitutionalism, and management science.